Van Bommel Van Dam prijs '85. (Venlo : Museum Van Bommel Van Dam, 1985)
Teeken, Toon ; Dieleman, Piet ; Van der Pol, Jan ; Tolman, Ronald ; Wehrens, Peter
Van Bommel Van Dam prijs '85, Museum Van Bommel Van Dam, Venlo, van 21 april tot en met 27 mei 1985
Nederlands
kunstcatalogus